Reawakening of large earthquakes in south central Chile: The 2016 Mw 7.6 Chiloé event. Issue 13 (3rd July 2017) - Ruiz, S.; Moreno, M.; Melnick, D.; del Campo, F.; Poli, P.; Baez, J. C.; Leyton, F.; Madariaga, R.
Abstract: On 25 December 2016, the M w 7.6 Chiloé earthquake broke a plate boundary asperity in south central Chile near the center of the rupture zone of the M w 9.5 Valdivia earthquake of 1960. To gain insight on decadal‐scale deformation trends and their relation with the Chiloé earthquake, we combine geodetic, teleseismic, and regional seismological data. GPS velocities increased at continental scale after the 2010 Maule earthquake, probably due to a readjustment in the mantle flow and an apparently abrupt end of the viscoelastic mantle relaxation following the 1960 Valdivia earthquake. It also produced an increase in the degree of plate locking. The Chiloé earthquake occurred within the region of increased locking, breaking a circular patch of 15 km radius at 30 km depth, located near the bottom of the seismogenic zone. We propose that the Chiloé earthquake is a first sign of the seismic reawakening of the Valdivia segment, in response to the interaction between postseismic viscoelastic relaxation and changes of interseismic locking between Nazca and South America. Key Points: The 2016 Chiloe earthquake is a sign of the seismic reactivation of the south central Chile megathrust after the M w 9.5 earthquake of 1960 South central Chile has been affected by postseismic viscoelastic relaxation and superinterseismic locking after the 2010 Maule earthquake The Chiloe earthquake broke an 15 km radius area at 30 km depth, near the bottom of the seismogenic zone